Characteristics of Children with Asthma Who Achieved Remission of Asthma - Javed, Asma (2013)
OBJECTIVE: To characterize two groups of asthmatics who had achieved remission and those who had not achieved remission of asthma. METHODS: The study was a retrospective cohort study based on 117 asthmatic children who participated in a previous study. We categorized the children into two groups: asthmatics with remission versus asthmatics without remission. We defined remission of asthma as lack of symptoms/signs of asthma or asthma-related medications or health care services for at least three consecutive years. Long-term remission was defined by no relapse of asthma after achieving remission. We characterized these groups. RESULTS: Of the 117 subjects, 70 (60%) were male, 91 (78%) were Caucasians, and the mean age at index date of asthma was 8.1 years. A total of 59 asthmatic children (50%) achieved remission and 28 asthmatics (24%) achieved long-term remission. Asthmatics with remission were more likely to be Caucasian (87%) compared to those without (69%) (p = .039) There were no differences in the frequency of visits for viral (0.3 vs. 0.4 per person-years, p = .29) or bacterial infections (0.7 vs. 0.5 per person-years, p = .49) between asthmatics with and without remission. Gender, socioeconomic status, smoking exposure, family history of asthma or atopy, breastfeeding history, peak flow meter availability, asthma action plan, and influenza vaccinations were not associated with remission. CONCLUSIONS: Only half of asthmatic children accomplished remission of asthma ever and 24% of asthmatic children had long-term remission. Ethnicity may affect remission of asthma but microbial infections may not influence the likelihood of remission of asthma and vice versa.